The relationship between neuroticism and life expectancy with addiction potential tendency in male high school students - Alireza Agha Yousefi; Majid Saffarniya; Ommolbanin Roodbari; Hadis Saeedi; Kouros Divsalar; Fatemeh Eslamian (Islamic Azad University, 2015)
Introduction: Addiction to narcotics is one of disasters that threatens humans' life especially adolescents. In addition, narcotic abuse is related to many dangerous behaviors such as destroying the private properties, increasing the violence and treacherous sexual behaviors and infectious diseases like AIDS, increasing mental disorders and suicide thoughts. The aim of the current research was to analyze the relationship between neuroticism and life expectancy with addiction potential tendency in male high school students. Methods: Research subjects were 242 male students that were chosen from 13 high school students in Anbarabad city. In order to gather data, NEO Five-Factor Inventory (NEO-FFI), Snyder's life expectancy questionnaire, and Vide and Bucher's addiction potential tendency questionnaire, were used. Data were analyzed using Pearson correlation methods and regression analysis. Results: Findings showed a negative and significant relationship between life expectancy and addiction potential tendency. Also, there was a significant positive relationship between neuroticism and addiction potential tendency (P < 0.001). Life expectancy predicted 31% and neuroticism 42% variance mark of addiction potential tendency. Conclusion: Based on the results, it can be concluded that decreasing neuroticism and increasing life expectancy can be a protecting shield against addiction potential tendency.